Price dependency and spillover effects in global crude oil markets - Zhang, Han (2017)
The content of this thesis is the result of a comprehensive study about global spot crude oil markets. Using a large data set including 32 crude varieties, this thesis analyzes price dependency, return and volatility spillover effects, and explores the driving forces behind such spillover effects.